Integrated Empowerment Strategy of Indigenous Communities and Local Communities Based on the Blue Economy in East Fakfak District, Fakfak District - Ismail, R. Moh.; Arbakala, Jani; Jumadi, Jumadi; Soedrijanto, Angky (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
The process of the socio-cultural mix between the indigenous people of the Mbaham tribe who live in the East Fakfak district, which is very rich in natural resource potential, and the local community, which basically also comes from immigrants, has been going on for generations in the population structure. The research aims to find a form of empowerment strategy that prioritizes integration between the indigenous people of the Mbaham tribe and local communities in order to build a blue economy in the East Fakfak district to improve people's lives. This descriptive research uses a combined quantitative and qualitative approach based on empirical survey results, carried out in six villages in the East Fakfak district during 2022. The results show that the socio-cultural mix has the potential to be very strong and open to generating broader synergies in the form of building a global communication network , which allows investment to enter the East Fakfak district. The advanced attitude and thinking of the leaders of the Mbaham tribal people in the East Fakfak district which are already advanced can open up opportunities for the development of an integrated and sustainable blue economy.